Successful Treatment of Testicular Pain With Peripheral Nerve Stimulation of the Cutaneous Branch of the Ilioinguinal and Genital Branch of the Genitofemoral Nerves. Issue 2 (18th January 2012) - Rosendal, Frederikke; Moir, Liz; de Pennington, Nick; Green, Alexander L.; Aziz, Tipu Z.
<x xml:space="preserve">Abstract</x> Objectives: To assess the effect of peripheral nerve stimulation on neuropathic testicular pain. Material and Methods: A 30‐year‐old man with a four‐year history of chronic testicular pain following scrotal hydrocele surgery had two percutaneous leads implanted in his groin and low‐frequency stimulation of the cutaneous branch of the ilioinguinal and genital branch of the genitofemoral nerves. Result: At seven‐month follow‐up, the pain intensity had declined from 9/10 to 2/10 on the numeric rating scale. Conclusion: We report the successful implantation of an ilioinguinal and genitofemoral nerve stimulator for sustained suppression of intractable neuropathic testicular pain.